Ensuring Land Status Security to Accelerate the Rejuvenation of Small-Scale Oil Palm Plantations in Indonesia - Mutiara Panjaitan; Agus Sardjono; Harsanto Nursadi (Unissula, 2024)
This study examines the role of land status in accelerating the Small-scale Palm Oil Rejuvenation (Peremajaan Sawit Rakyat or PSR) program in Indonesia, particularly in light of the Job Creation Law and its derivative regulations. The research aims to evaluate the effectiveness of these legal provisions in addressing challenges within the palm oil sector, especially for small farmers, by ensuring land status certainty. A normative legal research approach, utilizing NVivo 12 Plus software for data analysis, was employed to analyze secondary data from regulations, journal articles, government reports, and online media. The study finds that resolving land status issues is crucial for the effective implementation of the PSR program, highlighting the need for improvements in geospatial data support, synchronization of statutory regulations, and coordination among ministries and local governments. The results emphasize the importance of continuous policy review and legal adjustments to overcome the complexities of land tenure in the palm oil industry. This research provides practical insights for stakeholders to reform land policies and enhance the implementation of the PSR program, ultimately contributing to the growth and sustainability of smallholder palm oil plantations in Indonesia.